A Comprehensive Review of Ayurvedic and Modern Surgical Approaches in the Treatment of Bhagandara (Fistula in Ano) (AYUSHDHARA, 2024)
One of the most common conditions affecting the anorectal region is Bhagandara i.e., fistula-in-ano. The "Father of Surgery," Acharya Sushrut, described this condition as one of the Ashtamahagada (eight major diseases) in ancient Ayurvedic literature. Fistula-in-ano is a challenging anorectal disorder, notorious for its high recurrence rates despite various available surgical interventions in modern medicine. Among the treatment modalities, the Ayurvedic para-surgical procedure, Ksharasutra, has been recognized for its effectiveness in managing fistula-in-ano with significantly lower recurrence rates than conventional surgical methods. This review article compiles and synthesizes the scattered descriptions of Bhagandara across various Ayurvedic and modern surgical texts, tracing its understanding from ancient times, as documented by Acharya Sushruta and other classical Samhitas. Moreover, this article discusses modern techniques, including modifications of classical Ayurvedic procedures, which target different levels of the fistulous tract to promote healing without complications or recurrence. While these methods show promise, further large-scale comparative clinical studies are needed to validate their efficacy in managing fistula-in-ano.